2015
DOI: 10.1097/qad.0000000000000860
|View full text |Cite
|
Sign up to set email alerts
|

Normal T-cell activation in elite controllers with preserved CD4+ T-cell counts

Abstract: Background HIV Elite controllers (EC) suppress HIV viremia without ART, yet previous studies demonstrated that EC maintain an activated T cell phenotype. Chronic immune activation has detrimental consequences and thus ART has been advocated for all EC. However, EC is not a clinically homogenous group. Since CD4% is among the best predictors of AIDS related events, in the current study, we assessed whether this marker can be used to stratify EC needing ART. Methods Sixteen EC were divided into 2 groups based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 56 publications
6
22
0
Order By: Relevance
“…There is a strong association between PD-1 and the immune activation marker Ki67 in CD4 + T cells from cART-treated individuals ( 29 , 42 ). Consistent with these data, reduced PD-1 expression correlates with lower immune activation in HIV-elite controllers, the HIV + infected individuals with immune control of viral loads ( 46 , 47 ). Transcriptomic analyses of PD-1 + cells isolated from blood also suggest a significant increase in IFN-γ response genes and IL-6 response genes in INR with higher immune activation, compared to IR with lower immune activation (Figure 1 ).…”
Section: Immune Activation Correlates To Increased Hiv Reservoir Sizesupporting
confidence: 75%
See 1 more Smart Citation
“…There is a strong association between PD-1 and the immune activation marker Ki67 in CD4 + T cells from cART-treated individuals ( 29 , 42 ). Consistent with these data, reduced PD-1 expression correlates with lower immune activation in HIV-elite controllers, the HIV + infected individuals with immune control of viral loads ( 46 , 47 ). Transcriptomic analyses of PD-1 + cells isolated from blood also suggest a significant increase in IFN-γ response genes and IL-6 response genes in INR with higher immune activation, compared to IR with lower immune activation (Figure 1 ).…”
Section: Immune Activation Correlates To Increased Hiv Reservoir Sizesupporting
confidence: 75%
“…While it is unclear, how increased proliferation and HIV reservoir size are linked, these data suggest that increased T-cell proliferation might also provide a mechanism for the maintenance of the HIV reservoir. Increased cycling and higher Ki67 protein expression further correlate with higher expression of PD-1, a marker that can be up-regulated as a result of homeostatic or antigen-induced proliferation, and T-cell exhaustion ( 43 46 ). There is a strong association between PD-1 and the immune activation marker Ki67 in CD4 + T cells from cART-treated individuals ( 29 , 42 ).…”
Section: Immune Activation Correlates To Increased Hiv Reservoir Sizementioning
confidence: 96%
“…The factors involved in the immunological progression observed in some ECs that maintain virological control are largely unknown and studies addressing this issue are scarce, with only a few investigating potential associated immunological factors [ 10 , 15 , 36 , 37 ]. In some of these studies, T-cell activation was shown to be associated with disease progression in ECs using a cross-sectional design [ 15 , 36 ]. The other two studies addressing the association of T-cell activation with CD4 evolution in EC patients and using a longitudinal follow-up period similar to our study [ 10 , 37 ] found discordant results.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this evidence, some studies suggest that the cART might lead to a marked decrease in immune activation and increased CD4 + T cell counts in ECs, reducing the risk of non-AIDS-related events ( 6 8 ). Conversely, other studies describe that elevated levels of T cell activation and soluble inflammation markers are not associated with a faster rate of CD4 + T cell decline in ECs ( 9 , 10 ) or that ECs maintain absolute CD4 + T cell counts and T cell activation levels within the normal range over time ( 10 12 ), thus concluding that these individuals may not have benefited from early cART initiation.…”
Section: Introductionmentioning
confidence: 96%